Multiple-Antibiotic Resistance Mediated by Structurally Related IncL/M Plasmids Carrying an Extended-Spectrum β-Lactamase Gene and a Class 1 Integron - Villa, Laura (American Society for Microbiology, 2000)
A conjugative IncL/M plasmid (pSEM) conferring resistance to gentamicin, amikacin, kanamycin, sulfonamides, and expanded-spectrum cephalosporins was found in pathogenic strains of Salmonella enterica serotype Typhimurium. Resistance to aminoglycosides was encoded by a sul1-type class 1 integron (In-t3). An extended-spectrum beta-lactamase gene, bla(SHV-5), was identified 3.5 kb downstream of the integrase (intI1) gene of In-t3. Nucleotide sequence analysis of the 5.3-kb bla(SHV-5)–In-t3 region of pSEM highlighted striking similarities with IncL/M plasmids isolated from nosocomial gram-negative pathogens, conferring resistance to expanded-spectrum cephalosporins and aminoglycosides.